The effect of deproteinization temperature on chitosan extraction from shrimp shell in Sabah - Saran Meru; Mohd Hafiz Abd. Majid; Newati Wid (e-VIBS, Faculty of Science and Natural Resources, 2024)
Chitosan is a straight amino-polysaccharide made after the alkaline deacetylation of biopolymer chitin. Nacetyl-D-glucosamine molecules are converted into D-glucosamine components, which contain free amino groups with an advantageous ionic charge. Chitosan and its derivatives have been used in a wide variety of applications such as food industry, biomedicine, cosmetics and agriculture. There are three stages to extract chitosan from shrimp shell waste such as deproteinization, demineralization and deacetylation. This present study aims to examine the influence of different temperatures and using 60% NaOH during the deproteinization process while 5% of HCl during demineralization and 60% NaOH during deacetylation. The temperature being studied during deproteination was 30 oC – 80 oC. The results show that the percentage of chitosan yield was higher when using low temperature at the first stage. The yield obtained in this study ranged from 6.90 – 9.50%, while degree of deacetylation ranged from 85.28 – 85.34%.